On a software tool for implementation of systolic algorithms in the cluster environment - Edmon M. Davtyan (Изд-во НАН РА)
In this paper a software tool SAS (Systolic Algorithm Simulator) is designed to model the work of a one-dimensional systolic array of n cells on a homogenous computational cluster of m ¿ n processors. As a result of the program execution, a cluster-based programming module is obtained, where computational resourses of the system are used in an e®ective way.
Keywords: Mathematics; Algorithm